Young people in Australia discuss strategies for preventing the normalisation of gambling and reducing gambling harm - Hannah Pitt; Samantha L. Thomas; Melanie Randle; Sean Cowlishaw; Grace Arnot; Sylvia Kairouz; Mike Daube (BMC, 2022)
Abstract Background The normalisation of gambling for young people has received considerable recent attention in the public health literature, particularly given the proliferation of gambling marketing aligned with sport. A range of studies and reports into the health and wellbeing of young people have recommended that they should be consulted and engaged in developing public health policy and prevention strategies. There are, however, very few opportunities for young people to have a say about gambling issues, with little consideration of their voices in public health recommendations related to gambling. This study aimed to address this gap by documenting young people's perceptions about strategies that could be used to counter the normalisation of gambling and prevent gambling related harm. Methods This study took a critical qualitative inquiry approach, which acknowledges the role of power and social injustice in health issues. Qualitative interviews, using a constructivist approach, were conducted with 54 young people (11-17 years) in Australia. Reflexive thematic analysis was used to interpret the data. Results Five overall strategies were constructed from the data. 1) Reducing the accessibility and availability of gambling products; 2) Changing gambling infrastructure to help reduce the risks associated with gambling engagement; 3) Untangling the relationship between gambling and sport; 4) Restrictions on advertising; and 5) Counter-framing in commercial messages about gambling. Conclusions This study demonstrates that young people have important insights and provide recommendations for addressing factors that may contribute to the normalisation of gambling, including strategies to prevent gambling related harm. Young people hold similar views to public health experts about strategies aimed at de-normalising gambling in their local communities and have strong opinions about the need for gambling to be removed from sport.